Motif II of Japanese Encephalitis Virus NS3 Protein is Not Essential for RNA Binding Activity - Utama, Andi; Shimidzu, Hiroyuki (Annales Bogorienses, 2007)
The role of motif II (DEAH; Asp285-Glu286-Ala287-His288) of Japanese encephalitis virus (JEV) NS3 protein on RNA binding activity was studied. A point mutation was introduced to the motif and the RNA binding activity of each mutant protein was analyzed. Truncated form of each protein with a His-tag was expressed m Escherichia coli BL21(DE3)pLysS and purified by metal affinity resin. Asp-285 and Glu-286 was respectively substituted with Ala. Ala-287 was replaced by Cys, Gly, or Ser. His-288 was mutated to other 19 amino acids. In total, 24 mutant proteins were produced and analyzed. As results, all mutants showed quite similar RNA binding activity indicating that motif II of JEV NS3 is not related to RNA binding activity. The same finding was reported for hepatitis C viruc (HVC) NS3 protein, suggesting lhe similar structure of NS3 protein in the flavivirus.